L'arbitrage CCJA - Wambo, Jérémie (Revue de l'ERSUMA, 2011)
L’arbitrage est désormais une institution traditionnelle de la vie des affaires sur le plan national, mais aussi et surtout sur le plan international. C’est un « mode alternatif de règlement des litiges qui consiste à faire trancher un différend par de simples particuliers », qui peuvent être des « personnes choisies par les parties »115. On distingue généralement deux types d’arbitrage, l’arbitrage Ad Hoc, qui demeure le plus fréquent, et l’arbitrage Institutionnel. Mais notre discussion va beaucoup plus porter sur le deuxième type d’arbitrage à travers le Centre d’arbitrage de la Cour Commune de Justice et d’Arbitrage de l’OHADA. Les signataires du Traité de Port Louis (Traité OHADA) du 17 Octobre 1993 avaient, dès le préambule, exprimé leur désir de « promouvoir l’arbitrage comme instrument de règlement des différends contractuels ». C’est pourquoi l’article 1er dudit Traité qui définit ses objectifs précise qu’il est question entre autres d’encourager le « recours à l’arbitrage pour le règlement des différends contractuels ». Les articles 21 à 25 posent les bases de cet arbitrage. La concrétisation de ces intentions s’est manifestée par l’adoption à Ouagadougou par le Conseil des Ministres de l’OHADA le 11 Mars 1999, de l’Acte Uniforme relatif au Droit de l’Arbitrage, et du Règlement d’Arbitrage de la CCJA qui fixe les règles applicables à l’arbitrage CCJA. Plusieurs textes ont été pris par la suite qui ont permis d’organiser l’arbitrage CCJA (I) afin de rendre lisible le professionnel le déroulement de procédure arbitrale.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Procédure arbitrale; Règlement d'arbitrage

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Mediação e judiciário: condições necessárias para a institucionalização dos meios autocompositivos de solução de conflitos - Gabbay, Daniela Monteiro (Universidade de São Paulo, 2011)
A questão central deste trabalho refere-se à institucionalização da mediação no âmbito do Judiciário e às condições necessárias para uma boa relação entre a mediação e o processo judicial. Esta questão foi analisada sob as perspectivas processual e institucional. A primeira recai sobre as bases do processo de mediação, em especial o devido processo legal mínimo, e a sua interação com o processo judicial, diferenciando a justiça do processo e a justiça do resultado. A segunda recai sobre o desenho dos programas de mediação que funcionam junto ao Judiciário e os papéis assumidos pelos diferentes atores que participam destes programas: juízes, mediadores, partes, advogados e funcionários dos Tribunais. Sob esta última perspectiva, foi realizada pesquisa empírica e comparada em programas de mediação que funcionam junto ao Judiciário no Brasil e nos EUA. The main issue of this work is the institutionalization of mediation within the Courthouse and the pre-conditions for having a good relationship between mediation and the Judiciary. This issue is analyzed from both procedural and institutional points of view. The procedural perspective falls on the mediation due process (minimal but meaningful due process standards) and on the differences between the procedural and substantial justices. The institutional perspective falls on the design of the Court-Connected Mediation Programs and on the roles of the players who participated in these programs: judges, mediators, plaintiff and defendant, attorneys, and Court workers. An empirical research was also done about the Court-Connected Mediation Programs in Brazil and in the United States.
Keywords: Arbitrage; Arbitragem; Arbitration; Court-connected mediation programs design; Empirical research; Institutionalization of mediation; Juizo arbitral; MARD; Mediación; Mediation; Mediação; Mediação e conciliação; Minimal due process; Médiation; Solução de conflito

Effectiveness and Remedies of the Arbitral Awards in OHADA’s System and in People’s Republic of China. - Samassekou, Mamoudou; Lianbin, Song (Journal of Politics and Law, 2011)
Today the arbitral justice has experienced an exceptional development. It is a universal phenomenon which requires the involvement of all economic and legal players of developed and developing countries.OHADA is a common business law and wish to secure legal security for regional and foreign economic agents by offering a vast economic space. The People’s Republic of China (PRC) is an emerging country which increases its economic outlets in a context of globalization. This natural interdependence will increase the scope of economic exchanges, which may generate some disputes in businesses. This article aims to compare two legal systems in the international commercial arbitration field: the legal system of OHADA and the PRC’s legal system; especially in the effectiveness and the remedies of the arbitrators’ decisions.

Le principe de compétence-compétence en droit de l'arbitrage - Boucaron-Nardetto, Magali (Université Nice Sophia Antipolis, 2011)
Dans son sens originaire, le principe compétence-compétence permet au tribunal arbitral, comme à tout juge, de statuer sur sa compétence. En droit français, il s’est transformé en règle de conflit entre justice publique et justice privée doublement originale : d’une part, il repose sur l’exercice coordonné du pouvoir de juger de la compétence ; d’autre part, il est pluraliste. Enclenché par l’apparence vraisemblable d’une convention d’arbitrage, le principe compétence-compétence consiste en un mécanisme composite se déployant dans le temps du procès arbitral et dans l’espace des deux ordres juridiques considérés. Ainsi, trois règles distinctes permettent à chacune des justices – justice française et justice arbitrale – de connaître de sa propre compétence de manière coordonnée. Tout d’abord, en amont et en parallèle de l’instance arbitrale, l’effet négatif de la compétence-compétence paralyse le pouvoir des juridictions étatiques de statuer sur leur compétence. Ensuite, le temps du procès arbitral, l’effet positif de la compétence-compétence des tribunaux arbitraux reconnaît à ces derniers le pouvoir de juger de leur compétence. Enfin, au stade post-arbitral, l’effet positif de la compétence-compétence des juridictions publiques permet à ces dernières de retrouver le pouvoir de statuer sur leur compétence lors des recours ouverts contre la sentence. Chacune des règles examinées connait limites ou écueils. Parfois, l’équilibre est rompu soit au profit des juridictions d’Etat, soit au profit des juridictions arbitrales. Force est de constater que le caractère pluraliste du principe compétence-compétence est tantôt réalité, tantôt mirage. In its original sense, the principle of competence-competence empowers the arbitral tribunal, as well as any judge, to decide on its own jurisdiction. Under French law, it has been transformed into a rule on conflict of jurisdiction between state court and arbitration tribunal doubly innovative. On one hand, it rests on the coordinated exercise of the power to rule on its jurisdiction; on the other hand, it is pluralist. Activated by the appearance of an arbitration agreement, the principle of competence-competence consists of a heterogeneous mechanism, using the time of arbitration proceedings and space of both legal orders. Thereby, three distinct rules allow each justice - French courts and arbitration - to rule on its own jurisdiction coordinately. First, during or prior the arbitration proceedings, the negative effect of the competence-competence paralyses the power of the state court to rule on its own jurisdiction. Secondly, during the arbitration proceedings, the positive effect of the competence-competence of the tribunal arbitral recognizes that arbitrators decide upon their own jurisdiction. Finally, at the post-arbitral stage, the positive effect of the competence-competence of state courts permits them to recover the power to rule on their own jurisdiction at the setting aside or enforcement stage of the arbitration. Each analyzed rule has its own limits. Sometimes, the balance is disrupted either in favour of state courts, or in favour of the arbitral tribunal. To conclude, it is clear that the pluralist character of the principle of competence-competence is in some cases a reality, in others a mirage.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Pluralisme juridique; Règlement de conflits

Dispute Resolution in International Electricity Trade - Han, Baoqing (Energy Procedia, 2011)
International electricity trade disputes can arise at three key levels: state to state; investor to state; private party to private party. Parties may be more open to submission of their disputes to international arbitration. However, they should make proper arbitration options according to the types of disputes. At the same time, considering the risks facing dispute resolution, it is imperative to specifically design effective tools to mitigate these risks.
Keywords: Dispute resolution; Disputes; International Arbitration; International electricity trade; Risk mitigation

L'annulation de la sentence arbitrale au Québec et dans l'espace OHADA : une approche comparée. - Kouassi, Fabrice Constant (Université de Sherbrooke, 2011)
Le processus de règlement des litiges par la voie de l’arbitrage a nourri des ambitions économiques énormes dans les sphères juridiques où ce mécanisme a été instauré. L’efficacité de ce processus qui signifie entre autre un processus ayant abouti à une application, voire une exécution effective des protagonistes est un gage de la réalisation de ces ambitions. Or, ce processus peut être compromis du fait de l’annulation de la sentence arbitrale par un juge dont l’intervention dans le processus peut soit le renforcer, soit l’annihiler fondamentalement. Cette situation explique dans une large mesure les raisons pour lesquelles la doctrine juridique se place en faveur d’une collaboration solide entre la justice publique et la justice privée de l’arbitrage. Comment cette question de l’annulation de la sentence arbitrale est abordée dans les sphères juridiques du Québec et de l’Ohada? Quels sont les effets juridiques issus de la comparaison de cette situation dans chacune de ces sphères? Telle se présente la substance de cette recherche dont la méthode comparative est alimentée par le paradigme de l’herméneutique juridique et son corollaire le pluralisme juridique. Les résultats issus du dialogue comparatif devraient participer à une amélioration des situations problématiques décelées dans les sphères concernées. The rule process of lawsuits based on arbitration has filled out huge economic ambitions related to judicial spheres where this mechanism has been established. The efficiency of this process, which among others, has led to an application, indeed a real execution of the protagonists, is somewhat a guarantee to the fulfilment of these ambitions. However, this process can be compromised because of the cancellation of the arbitral sentence by a judge whose intervention in the process can either reinforce it or destroy it. This situation mainly explains the reasons why the juridical doctrine is in favour of a solid collaboration. How do the juridical sphere of Quebec and Ohada tackle this issue of the cancellation of the arbitral sentence? What are the juridical effects stemmed from the comparism of this situation in both spheres? The way the substance of this research appears and whose comparative method is fed by the paradigm of the juridical hermeneutics and its juridical pluralism corollary. The results stemmed from the comparative dialog should participate in improving problematic situations detected in the applied spheres.
Keywords: Annulation; Arbitrage; Arbitragem; Arbitration; Litiges; Sentence arbitrale

Arbitration: One Size Does Not Fit All: Necessity of Developing Institutional Arbitration in Developing Countries - Namrata Shah, Niyati Gandhi (Journal of International Commercial Law and Technology, 2011)
Litigation in developing countries has many defects which has prompted a need for the development of alternative dispute resolution mechanisms. Arbitration, being one such substitutive mechanism as a type of private litigation is the most suitable for the same. This paper deals with the need to develop institutional arbitration to co-exist with ad hoc arbitration and scale it down to be available for dispute resolution in developing countries using an illustration of India. Certain recommendations to make institutional arbitration, which is considered to be appropriate for International commercial dispute resolution, suitable for domestic disputes in developing countries have been highlighted.
Keywords: Arbitrage; Arbitragem; Arbitration; Developing countries; Institutional arbitration

Les MARC en OHADA (Journal africain du droit des affaires, 2011)
GENERALITES SUR LES MARC La justice arbitrale La médiation commerciale : une alternative au système judiciaire L’utilité de l’expertise Interactions entre médiation et arbitrage LES MARC EN OHADA Approche culturelle des MARC en OHADA Regards franco-africains sur les étapes de la médiation commerciale La gestion d’une procédure d’arbitrage : vue d’un opérateur économique de l’espace OHADA Analyse comparée du droit de l’arbitrage OHADA et du droit international L’arbitrage de la Cour Commune de Justice et d’Arbitrage (CCJA) de l’OHADA Nouveau Règlement de médiation de la Cour d’Arbitrage de Côte d’Ivoire (CACI)
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Mediation; Médiation

L'arbitre international : étude de droit comparé - Partida, Sebastián (Université Paris 2, 2011)

A comparative study: Arbitration agreement in OHADA and People's Republic of China arbitration laws - Samassekou, Mamoudou; Song, Lianbin (Journal of Politics and Law, 2011)
This article aims to compare the arbitration agreement of the OHADA legal system to that of the People's Republic of China. In the Chinese legal system the parties to a contract are required to have an arbitration agreement written before the occurrence of any incident in the execution of their contract. The parties must specify in advance, in the said agreement, the chosen arbitration institution for potential disputes. In the OHADA legal system, the parties are free to decide before or during execution of the contract of an arbitration agreement. They may also decide whether in case of a dispute, they would want to refer to an institutional arbitration or an ad hoc arbitration. According to the chosen legal system the consequences are different.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration Agreement; China-OHADA